2014
DOI: 10.1111/petr.12252
|View full text |Cite
|
Sign up to set email alerts
|

Delayed graft function in pediatric deceased donor kidney transplantation: Donor‐related risk factors and impact on two‐yr graft function and survival: A single‐center analysis

Abstract: There is mounting evidence that the quality of organs from cadaver donors may be influenced by events occurring around the time of brain death. Aim of this present study was to analyze the correlation of DGF with brain-dead donor variables in a single-center pediatric population and to evaluate DGF influence on patients- and grafts outcome. End-points of the study were DGF prevalence, DGF donor-related risk factors, graft function, patient- and graft survival rate, respectively, at six, 12, and 24 months FU. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Post-KAS recipients spent more time receiving dialysis (median 1.26 vs 1.07 years, P = .02), were more likely to have 100% cPRA (2.0% vs 0.1%, P = .001), and were equally like to have ≤3 mismatches with their donor (17.1% vs 16.1%, P = .5). Donor age increased slightly post-KAS (median [IQR] 22 years [18][19][20][21][22][23][24][25][26][27][28][29] vs 22 years [17][18][19][20][21][22][23][24][25][26][27], P < .001), and post-KAS recipients were less likely to receive an organ from a pediatric donor (22.6% vs 28.1%, P < .01). CIT was not significantly different between groups (median 11.6 vs 11.5 hours, P = .3), nor was KDPI (median 12 vs 11, P = .4).…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-KAS recipients spent more time receiving dialysis (median 1.26 vs 1.07 years, P = .02), were more likely to have 100% cPRA (2.0% vs 0.1%, P = .001), and were equally like to have ≤3 mismatches with their donor (17.1% vs 16.1%, P = .5). Donor age increased slightly post-KAS (median [IQR] 22 years [18][19][20][21][22][23][24][25][26][27][28][29] vs 22 years [17][18][19][20][21][22][23][24][25][26][27], P < .001), and post-KAS recipients were less likely to receive an organ from a pediatric donor (22.6% vs 28.1%, P < .01). CIT was not significantly different between groups (median 11.6 vs 11.5 hours, P = .3), nor was KDPI (median 12 vs 11, P = .4).…”
Section: Study Populationmentioning
confidence: 99%
“…DGF is an important outcome to study because it is associated with worse posttransplant outcomes, including acute rejection and graft failure. [25][26][27][28] Moreover, it is a relatively more common complication after DDKT, such that any differences in its incidence after KAS should be readily apparent. Our finding of no statistically significant difference in DGF rates after KAS is in contrast to a study that reported a 69% increase in the odds of DGF for pDDKT recipients <10 years old.…”
Section: Ta B L Ementioning
confidence: 99%
“…First, the true value of an allocation system is best measured with graft and patient survival, but it is too early to use these measures to assess the impact of KAS. Instead, we use DGF, a known surrogate for graft survival confirmed to be independently associated with graft failure in our sample, 9,10 Semiparametric decomposition of the increased odds of DGF post-KAS via the DiNardo, Fortin, and Lemieux method. This method uses a propensity score and inverse probability weighting to estimate the counterfactual outcome if post-KAS recipients had received kidneys from the same donors with the same amount of dialysis time as pre-KAS recipients.…”
Section: Study Limitationsmentioning
confidence: 99%
“…8 In adults, the most important DGF risk factors include cold ischemic time (CIT), 3,[9][10][11][12][13][14] warm ischemic time (WIT), 3,14 donor age, 3,10,13 donor BMI, 3 recipient size/age, 3,10,15,16 length of prior dialysis, 10 terminal serum creatinine (SCr), 3,12 and kidney donation after circulation death kidney. 3 There are comparatively very few reports that delineate DGF risk factors in children, but they include prolonged CIT, 14,17 increased donor age 18 and primary FSGS diagnosis. 19 DGF is associated with poorer graft function, acute rejection, graft failure, and death, 2,3,5,6,17,18 and these risks are accentuated with longer DGF duration.…”
Section: Introductionmentioning
confidence: 99%
“…3 There are comparatively very few reports that delineate DGF risk factors in children, but they include prolonged CIT, 14,17 increased donor age 18 and primary FSGS diagnosis. 19 DGF is associated with poorer graft function, acute rejection, graft failure, and death, 2,3,5,6,17,18 and these risks are accentuated with longer DGF duration. 4,20,21 However, the incidence of DGF in children after transplant is relatively low (4-10%).…”
Section: Introductionmentioning
confidence: 99%